A phase II study of dose‐dense and dose‐intense ABVD (ABVDDD‐DI) without consolidation radiotherapy in patients with advanced Hodgkin lymphoma. (27th March 2014) - Russo, Filippo; Corazzelli, Gaetano; Frigeri, Ferdinando; Capobianco, Gaetana; Aloj, Luigi; Volzone, Francesco; De Chiara, Annarosaria; Bonelli, Annamaria; Gatani, Tindaro; Marcacci, Gianpaolo; Donnarumma, Daniela; Becchimanzi, Cristina; et al.
Summary We explored activity and safety of a dose‐dense/dose‐intense adriamycin, bleomycin, vinblastine and dacarbazine regimen (ABVDDD‐DI) in 82 patients with advanced Hodgkin Lymphoma. Patients entered a two‐stage Bryant‐Day Phase II study to receive six cycles of ABVDDD‐DI without consolidation radiotherapy. Cycles were supported with granulocyte colony‐stimulating factor and delivered every 21 d; drugs were administered on days 1 and 11 at the same doses of standard ABVD except for doxorubicin (35 mg/m2; first four cycles only). Co‐primary endpoints were complete response (CR) rate and severe acute cardiopulmonary toxicity; secondary endpoints were event‐free (EFS) and disease‐free survival (DFS). All patients received the four doxorubicin‐intensified courses and 96% concluded all six cycles (82·3% within the intended 18 weeks). This translated into a 66·9% increase of received dose‐intensity for doxorubicin and 31·8% for the other agents over standard ABVD. The CR rate was 95·1% (78/82) and 87·8% (72/82) achieved a metabolic CR after two cycles. Cardiopulmonary toxicity never exceeded grade 2 and affected 14·6% of patients. Most frequent toxicities were grade 4 neutropenia (10%) and anaemia (9%), grade 3 infection (17%) and grade 2 mucocutaneous changes (30%). Five‐year EFS and DFS was 88·3% and 93·7%, respectively. ABVDDD‐DI regimen was well‐tolerated and ensured substantial CR and EFS rates without radiotherapy.